Letter from J. Piper to James Curtis Booth, July 14, 1853 - Piper, Jason (1853)
Jason Piper invites James Curtis Booth (1810-1888) to a meeting of the Elk Ridge Agricultural Club.
Keywords: Booth, James Curtis, 1810-1888; Maryland--Elk Ridge; Private clubs; Societies